The Impact of Dietary Intake of Furocoumarins and Furocoumarin-Rich Foods on the Risk of Cutaneous Melanoma: A Systematic Review - Kaiser, Isabelle; Rappl, Anja; Bolay, Lena; Pfahlberg, Annette Bettina; Heppt, Markus; Gefeller, Olaf (Nutrients, 2025)
Background/Objectives: Furocoumarins, chemical compounds found in many plant species, have a photosensitizing effect on the skin when applied topically and, by interacting with ultraviolet radiation (UVR), stimulate melanoma cells to proliferate. Whether dietary intake of furocoumarins acts as a melanoma risk factor has been investigated in several epidemiological studies, which are synthesized in our systematic review. Methods: The study protocol was registered with PROSPERO (registration number: CRD42023428596). We conducted an in-depth literature search in three databases coupled with forward and backward citation tracking and expert consultations to identify all epidemiological studies, irrespective of their design, addressing the association between a furocoumarin-containing diet and melanoma risk. We extracted information on the study details and results in a standardized manner and evaluated the risk of bias of the results using the Joanna Briggs Institute’s critical appraisal tools. Results: We identified 20 publications based on 19 different studies providing information on the association between dietary furocoumarin intake and melanoma risk. We refrained from a meta-analytical synthesis of the results because of the large heterogeneity in exposure assessment, operationalization of furocoumarin intake in the analyses, and analytical methods of the studies. In a qualitative synthesis, we found moderate evidence supporting the notion that dietary furocoumarin intake at higher levels acts as a risk factor for cutaneous melanoma. Conclusions: Our systematic review provides an overview of the current epidemiological evidence, but it could not clearly answer whether and to what extent dietary furocoumarin intake increases melanoma risk. Future epidemiological analyses focusing on this topic require more comprehensive dietary and UVR exposure data to better characterize the individual total furocoumarin intake and its interplay with UVR exposure patterns.
CRIS-Team Scopus Importer:2025-05-02
Keywords: citrus fruits; cutaneous melanoma; diet; furocoumarin; grapefruits; ultraviolet radiation